Antiviral Activity of CD437 Against Mumps Virus - Kato, Fumihiro; Nakatsu, Yuichiro; Murano, Keiko; Wakata, Aika; Kubota, Toru; Hishiki, Takayuki; Yamaji, Toshiyuki; Kidokoro, Minoru; Katoh, Hiroshi; Takeda, Makoto (Frontiers in Microbiology, 2021)
Many efforts have been dedicated to the discovery of antiviral drug candidates against mumps virus (MuV); however, no specific drug has yet been approved. The development of efficient screening methods is a key factor for the discovery of antiviral candidates. In this study, we evaluated a screening method using an aequorea coerulescens green fluorescent protein-expressing MuV infectious molecular clone. The application of this system for the screening of active compounds against MuV replication revealed that CD437, a retinoid acid receptor agonist, has anti-MuV activity. The point of antiviral action was a late step(s) in the MuV lifecycle. Replication of other paramyxoviruses was also inhibited by CD437. The induction of retinoic acid-inducible gene (RIG)-I expression is a reported mechanism for the antiviral activity of retinoids, but our results indicated that CD437 did not stimulate RIG-I expression. Indeed, we observed antiviral activity despite the absence of RIG-I, suggesting that CD437 antiviral activity does not require RIG-I induction.